NILAI-NILAI EDUKASI DALAM KOMUNIKASI ISLAM - Ahdar Ahdar (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
The process of effective communication depends on the principles of credibility (trust), attractiveness, and power. Then the content (meaningful message to receiver), clarity (clarity of message), continuity (repetition), channels (channels of communication) and the capability of the audience. These principles can also be applied in the educational process of learning communication. In the whole process of education, teaching and learning activities are the most basic activities. Here, it means that the success or failure of educational goals depends on how teaching and learning processes are undertaken by the students and teachers. The effective learners can be measured from indicators such as personality, attitude, experience and ability to reach the goal. This opinion illustrates that educators can successfully carry out their duties if they have a good personality, intelligence, and ability to communicate.